A reinvestigation of spermiogenesis in Amphilina foliacea (Platyhelminthes: Amphilinidea) - Brunanská, Magdaléna; Poddubnaya, Larisa G; Xylander, Willi E R (Folia parasitologica, 2013)
Spermiogenesis in the amphilinidean cestode Amphilina foliacea (Rudolphi, 1819) was examined using transmission electron microscopy. The orthogonal development of the two flagella is followed by a flagellar rotation and their proximodistal fusion with the median cytoplasmic process. This process is accompanied by extension of both the mitochondrion and nucleus into the median cytoplasmic process. The two pairs of electron-dense attachment zones mark the lines where the proximodistal fusion of the median cytoplasmic process with the two flagella takes place. The intercentriolar body, previously undetermined in A.foliacea, is composed of three electron-dense and two electron-lucent plates. Also new for this species is the finding of electron-dense material in the apical region of the differentiation zone at the early stage of spermiogenesis, and the fact that two arching membranes appear at the base of the differentiation zone only when the two flagella rotate towards the median cytoplasmic process. The present data add more evidence for a close relationship between the Amphilinidea and the Eucestoda.
Keywords: Cestoda; ryby; spermatogeneze; Fishes; Male; Fish Diseases; Animals; Spermatogenesis; mužské pohlaví; Testis; zvířata; nemoci ryb; testis